Approaches and Practices of Product Innovation in Rongchang Grass Cloth Through the Intervention of Modern Design Language - Xi, Pei (Art and Society, 2025)
In the context of cultural confidence and consumption upgrading, the revitalization of intangible cultural heritage urgently needs to transition from productive protection to innovative development. This paper takes Rongchang Grass Cloth from Chongqing as its research subject, focusing on the core issue of how modern design language can systematically intervene in its product innovation. Through practice-oriented research methods and case analysis, this study identifies and proposes five core approaches through which modern design language intervenes in the product innovation of Rongchang Grass Cloth: symbol translation, material reconstruction, structural innovation, functional crossover, and narrative empowerment. The aim of this paper is to construct an effective design innovation methodology system, contributing to the theoretical framework for the contemporary transformation of Rongchang Grass Cloth and other similar intangible cultural heritage projects, ultimately promoting its creative return from cultural heritage to contemporary life aesthetics.